The demographics of dog bites due to K-9 (legal intervention) in the United States. (July 2019) - Loder, Randall T.; Meixner, Cory
Abstract: Background: There is sparse literature regarding K-9 (legal intervention) dog bites. It was the purpose of this study to analyze the demographics of K-9 dog bites using a national data base. Methods: This was a retrospective study of prospectively collected data from National Electronic Injury Surveillance System - All Injury Program for years 2005–2013. Patients with dog bites were identified and those due to legal intervention were analyzed. Statistical analyses were performed with SUDAAN 11.0.01™ software. A p < 0.05 was considered statistically significant. Results: There were an estimated 32, 951 K-9 dog bite ED visits, accounting for 1.1% of all ED dog bite visits. The K-9 group was nearly all male (95.0 vs 52.1%) and more commonly Black (42.0 vs 13.0%) compared to the non K-9 group. Bites to the head/neck and upper extremity were less frequent and lower extremity bites more frequent in the K-9 group; K-9 bites more commonly occurred outside the home. Within the K-9 group, the proportion of White patients increased with increasing age and smaller hospital size. Patients seen in small and medium size hospitals were in the middle age ranges, while those in the very young and >64 years of age were only seen at large hospitals. The average annual incidence of K-9 dog bites seen in the ED for US was 2.43 per 100, 000 males with no changes over time. Conclusions: In the US, 1.1% of all ED visits for dog bites are due to K-9 intervention with no change in incidence, even though this study spanned the time when it was encouraged to change K-9 intervention; from "find and bite" to "find and bark". The K-9 dog bite patient is nearly always male, more commonly Black, occurred away from home, and has a 3.7% hospital admission rate. Bites to the head/neck are less common compared to the non K-9 dog bite group. Highlights: K-9 dog bites account for 1.1% of all ED dog bite visits with no changes over time. K-9 dog bites typically occur in males; annual incidence is 2.4 per 100, 000 males. K-9 dog bites more frequently involve the lower extremity and occur outside the home.